The - Domjan, Michael
Known for its currency and clear writing style, this book provides a comprehensive and systematic introduction to elementary forms of learning that have been the focus of research for much of the twentieth century. The book covers habituation, classical conditioning, instrumental conditioning, stimulus control, aversive control, and their applications to the study of cognition and to the alleviation of behavior problems. Biological constraints on learning are integrated throughout the text, as are applications boxes that relate animal research to human learning and behavior. The book closely reflects the field of research it represents in terms of topics covered, theories discussed, and experimental paradigms described